2012
DOI: 10.1596/1813-9450-6021
|View full text |Cite
|
Sign up to set email alerts
|

Why Quality Matters: Rebuilding Trustworthy Local Government in Post-Conflict Sierra Leone

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 38 publications
1
41
0
Order By: Relevance
“…Estimation results further reveal that the relationship between attitude change and active listening is symmetric: people would mistrust local politicians who did not listen to their needs. Sacks & Larizza (2012) found that the quality of government services is a major contributing factor to political trust. Though my results do not provide any empirical support for the effects of public services, the non-finding may be explained by the use of different indicators.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation results further reveal that the relationship between attitude change and active listening is symmetric: people would mistrust local politicians who did not listen to their needs. Sacks & Larizza (2012) found that the quality of government services is a major contributing factor to political trust. Though my results do not provide any empirical support for the effects of public services, the non-finding may be explained by the use of different indicators.…”
Section: Key Findingsmentioning
confidence: 99%
“…Sacks & Larizza, 2012). Whether or not this relationship works through the channels they describe remains unclear and unproved.…”
Section: Introductionmentioning
confidence: 99%
“…Cassar, Grosjean, and Whitt (2013), Cuesta and Alda (2012), Luca and Verpoorten (2015), and Rohner, Thoenig, and Zilibotti (2013), yet there is only a handful of studies devoted to the topic of trust in government. These studies found that satisfaction with government services is a strong predictor of trust in government (Askvik, Jamil, and Dhakal, 2011;Hutchison and Johnson, 2011;Sacks and Larizza, 2012;Stoyan et al, 2016), a finding consistent with studies in developed countries.…”
Section: P O L I T I C a L T R U S T A N D S Tat E B U I L D I N Gsupporting
confidence: 86%
“…Sacks and Larizza (2012). Whether or not this relationship works through the channels they describe remains unclear and unproven.…”
Section: P O L I T I C a L T R U S T A N D S Tat E B U I L D I N Gmentioning
confidence: 99%
See 1 more Smart Citation